Biodiversity of cold seep ecosystems along the continental margin - Vanreusel, A.; Andersen, A.C.; Boetius, A.; Connelly, D.; Cunha, M.R.; Decker, C.; Hilario, A.; Kormas, K.A.; Maignien, L.; Olu, K.; Pachiadaki, M.; Ritt, B.; et al. (Oceanography, 2009)
During the European Commission’s Framework Six Programme, HERMES, we investigated three main areas along the European margin, each characterized by the presence of seep-related structures exhibiting different intensity of activity and biological diversity. These areas are: (1) the Nordic margin with the Håkon Mosby mud volcano and many pockmarks, (2) the Gulf of Cádiz, and (3) the eastern Mediterranean with its hundreds of mud volcanoes and brine pool structures. One of the main goals of the HERMES project was to unravel the biodiversity associated with these seep-associated ecosystems, and to understand their driving forces and functions, using an integrated approach. Several multidisciplinary research cruises to these three areas provided evidence of high variability in ecosystem processes and associated biodiversity at different spatial scales, illustrating the “hotspot” nature of these deep water systems.
NeMys doc_id: 17984